Language Policy vrs Language Reality in the Ghanaian Classroom: A Study of Colleges of Education - Fenyi, Kojo; Awukuvi, Enoch Mensah; Andoh, John; Pere, Francis K (EduLine: Journal of Education and Learning Innovation, 2021)
This descriptive qualitative study attempted to understand, explore and report the occasions and reasons for which a tutor or a student would use the native language in the second language classroom in a national language policy context, like Ghana, where such practice is disallowed. To use the L1 in the L2 classroom or not has been an ongoing debate in Applied Linguistics and Teaching English as Second/Foreign Language (TESL/TESOL, TEFL), in that, while a group insists on a strict monolingual English-only ESL classroom, another group thinks a reasonable quantity of L1 and appropriate use of same in the ESL classroom could actually facilitate the teaching and learning of English. Data collection instruments were participant observation and semi-structured interviews. Participants were 13 language tutors and 53 second-year language specialism students, all from four Colleges of Education, and selected through purposive sampling. Results revealed that L1 is used as functional strategy in the L2 classroom, and serves various reasons; empathy, classroom management, identity, lack of comprehension, nurturing bilingualism. It is recommended, therefore, that, the national language policy of Ghana which limits the language of classroom instruction to English be made lax enough to allow for some appreciable amount of the L1 to aid ‘understanding’, which is the bedrock of education.